2008
DOI: 10.1088/0957-4484/19/21/215704
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement in dye-sensitized solar cells based on MgO-coated TiO2electrodes by reactive DC magnetron sputtering

Abstract: A surface modification method was carried out by reactive DC magnetron sputtering to fabricate TiO(2) electrodes coated with insulating MgO for dye-sensitized solar cells. The MgO-coated TiO(2) electrode had been characterized by x-ray photoelectron spectroscopy (XPS), energy-dispersive x-ray spectroscopy (EDX), scanning electron microscopy (SEM), UV-vis spectrophotometer, cyclic voltammetry (CV) and electrochemical impedance spectroscopy (EIS). The study results revealed that the TiO(2) modification increases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(40 citation statements)
references
References 46 publications
1
38
1
Order By: Relevance
“…This leads to the increase in V oc after coating in DSSCs [11] . The reduction of V oc in our experiment, which is converse to the previous report [11,16] , is still under investigation. In addition, it can be found that the MgO layer is benefit for the f F and efficiency of the cell due to the energy barrier formed by the thin MgO layer.…”
Section: Characterization Of Electrodescontrasting
confidence: 49%
See 1 more Smart Citation
“…This leads to the increase in V oc after coating in DSSCs [11] . The reduction of V oc in our experiment, which is converse to the previous report [11,16] , is still under investigation. In addition, it can be found that the MgO layer is benefit for the f F and efficiency of the cell due to the energy barrier formed by the thin MgO layer.…”
Section: Characterization Of Electrodescontrasting
confidence: 49%
“…While elongating the dipping time to 30 min, η decreased to 4.80%. Wu et al [16] fabricated MgO-coated TiO 2 electrodes by reactive DC magnetron sputtering and investigated the influence of sputtering MgO for different times on the performance of DSSC. The TiO 2 electrode sputtering MgO for 3 min electrode has the highest efficiency, and the parameters of the cells decrease when the sputtering time was extended to 30 min.…”
Section: Characterization Of Electrodesmentioning
confidence: 99%
“…Using these parameters mentioned above, researchers can compare electron transport and diffusion property at different photoanodes in DSSC, such as photoanodes made of different materials (e.g., TiO 2 or combined oxides) [79][80][81][82][83][84][85][86][87], different morphologies and different structures (e.g., nanoparticles, nanotubes, nanorods, or complex structures) [88][89][90][91][92][93][94][95][96], different crystal forms (e.g., anatase and rutile for TiO 2 ) [97], and different substrates (e.g., rigid or flexible) [90,98]. For instance, we used EIS to compare two different microspheres photoanode-based DSSC, and the obtained Nyquist plots were shown in Fig.…”
Section: Electrochemical Impedance Spectroscopymentioning
confidence: 99%
“…Palomares et al compared the use of ultra-thin Al 2 O 3 , ZrO 2 and SiO 2 as ultra-thin blocking layers and all cells using these materials showed equal or better performance than with a TiO 2 blocking layer, with the best performance for Al 2 O 3 [126]. Other oxides used as blocking layers for DSSC include Nb 2 O 5 [127] and MgO [128].…”
Section: Dye Sensitized Solar Cellsmentioning
confidence: 99%